A proposal for monitoring the process of internalization following Galperin's conception - Rivera Valdez, Leonardo Daniel; López Cortés, Vicente Arturo; García Flores, Marco Antonio (Frontiers in Psychology, 2023)
Since Piaget and Vygotsky, private speech (PS) has been widely discussed, but in recent years the avenues for its study have greatly expanded. In this study, we explore the use of a re-coding scheme of PS inspired in the works of Pyotr Galperin. A coding scheme of PS as the form of action (FA) is proposed (i.e., external social speech, external audible speech, inaudible speech, and mental). An exploratory study was conducted to elucidate the appropriateness of the coding scheme ontogenetically and during tasks. Results showed that both, the coding scheme by type of speech and by FA, were adequate for differentiating ontogenetically between children. But only the coding schemes of the FA were appropriate for differentiating between children as a function of their performance (i.e., time and scores) in a Tower of London task. In fact, it was found that Galperin’s scheme was more suitable when there is redundancy in performance between those with audible and inaudible external speech.